2008
DOI: 10.1093/rpd/ncn288
|View full text |Cite
|
Sign up to set email alerts
|

Indoor radon and childhood leukaemia

Abstract: This paper summarises the epidemiological literature on domestic exposure to radon and risk for childhood leukaemia. The results of 12 ecological studies show a consistent pattern of higher incidence and mortality rates for childhood leukaemia in areas with higher average indoor radon concentrations. Although the results of such studies are useful to generate hypotheses, they must be interpreted with caution, as the data were aggregated and analysed for geographical areas and not for individuals. The seven ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 24 publications
2
25
1
Order By: Relevance
“…As infections and most of the environmental agents possibly related to the risk of childhood leukemia, like ionizing radiation due to domestic exposure to radon [25], air pollutants [26] or pesticides [27], are spatially heterogeneously distributed, it is conceivable that childhood leukemia also shows a tendency to spatial clustering with a temporal component. Thus, spatial and space-time analysis of the distribution of childhood leukemia might give a hint to environmental agent(s), possibly infections, which are involved in the etiology of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…As infections and most of the environmental agents possibly related to the risk of childhood leukemia, like ionizing radiation due to domestic exposure to radon [25], air pollutants [26] or pesticides [27], are spatially heterogeneously distributed, it is conceivable that childhood leukemia also shows a tendency to spatial clustering with a temporal component. Thus, spatial and space-time analysis of the distribution of childhood leukemia might give a hint to environmental agent(s), possibly infections, which are involved in the etiology of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Geographical correlations between residential radon and childhood leukemia have been shown in several studies [1,2]. We have previously reported that domestic radon exposure is significantly associated with the risk of childhood acute lymphoblastic leukemia [3].…”
Section: Introductionmentioning
confidence: 79%
“…The case-control study design has previously been described in detail [1]. In the present study, we included children (below age 15 years) registered in the Danish Cancer Registry [14] from 1968 to 1994 with a diagnosis of leukemia, and two control children matched individually by sex and birthday.…”
Section: Methodsmentioning
confidence: 99%
“…70 Another study from Denmark suggested that domestic radon exposure increases the risk of ALL. 71 By contrast, most recent studies have found no associations with domestic exposure to gamma radiation.…”
Section: Ionising Radiationmentioning
confidence: 99%